Occurrence and Quantification of Natural and Microplastic Items in Urban Streams: The Case of Mugnone Creek (Florence, Italy) - Valentina Rimondi; Alessio Monnanni; Eleonora De Beni; Gabriele Bicocchi; David Chelazzi; Alessandra Cincinelli; Sara Fratini; Tania Martellini; Guia Morelli; Stefania Venturi; Pierfranco Lattanzi; Pilario Costagliola (Toxics, 2022)
The terrestrial environment is an important contributor of microplastics (MPs) to the oceans. Urban streams, strictly interwoven in the city network and to the MPs’ terrestrial source, have a relevant impact on the MP budget of large rivers and, in turn, marine areas. We investigated the fluxes (items/day) of MPs and natural fibers of Mugnone Creek, a small stream crossing the highly urbanized landscape of Florence (Italy) and ending in the Arno River (and eventually to the Tyrrhenian Sea). Measurements were done in dry and wet seasons for two years (2019–2020); stream sediments were also collected in 2019. The highest loads of anthropogenic particles were observed in the 2019 wet season (109 items/day) at the creek outlet. The number of items in sediments increased from upstream (500 items/kg) to urban sites (1540 items/kg). Fibers were the dominant shape class; they were mostly cellulosic in composition. Among synthetic items, fragments of butadiene-styrene (SBR), indicative of tire wear, were observed. Domestic wastewater discharge and vehicular traffic are important sources of pollution for Mugnone Creek, especially during rain events. The study of small creeks is of pivotal importance to limit the availability of MPs in the environment.